2006
DOI: 10.1007/s00439-006-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage of human height is confirmed to 9q22 and Xq24

Abstract: Human height is an important and heritable trait. Our previous two genome-wide linkage studies using 630 (WG1 study) and an extended sample of 1,816 Caucasians (WG2 study) identified 9q22 [maximum LOD score (MLS)=2.74 in the WG2 study] and preliminarily confirmed Xq24 (two-point LOD score=1.91 in the WG1 study, 2.64 in the WG2 study) linked to height. Here, with a much further extended large sample containing 3,726 Caucasians, we performed a new genome-wide linkage scan and confirmed, in high significance, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Furthermore, they detected a second peak (LOD score 2.22, p = 0.001) on 9q33 and a third peak (LOD score 2.66, p = 0.0004) on 9q34. In addition, Liu et al (2006) confirmed the QTL for height on chromosome 9q22 in an extended data set. Based on our results and on those of the studies previously discussed, we suggest that chromosome region 9q22-qtel hosts at least one, possibly more, QTLs that are of importance for variation in adult height in populations of various ethnicities.…”
Section: Susceptibility Loci For Adult Heightsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, they detected a second peak (LOD score 2.22, p = 0.001) on 9q33 and a third peak (LOD score 2.66, p = 0.0004) on 9q34. In addition, Liu et al (2006) confirmed the QTL for height on chromosome 9q22 in an extended data set. Based on our results and on those of the studies previously discussed, we suggest that chromosome region 9q22-qtel hosts at least one, possibly more, QTLs that are of importance for variation in adult height in populations of various ethnicities.…”
Section: Susceptibility Loci For Adult Heightsupporting
confidence: 60%
“…These fairly low power estimates suggest that additional chromosome regions not detected in the current study might be of great importance for variation in adult height in the studied population. Since the first genome-wide linkage scans for height were performed in 2001 (Hirschhorn et al 2001;Perola et al 2001), several susceptibility loci for height have been reported [for a recent overview see Perola et al (2007)], but, as for most complex phenotypes, only some have been successfully replicated by further studies (Liu et al 2004(Liu et al , 2006Willemsen et al 2004;Sale et al 2005;Shmulewitz et al 2006). The most promising susceptibility loci for height (Score.Max p = 0.005) detected in our current study of sib-pairs from American Samoa was located on chromosome 9q31 at marker D9S1690.…”
Section: Susceptibility Loci For Adult Heightmentioning
confidence: 99%
“…Regions identified here attain high significance levels and can be replicated in various populations (28,30). Among the regions with the highest significance are chromosomes 9q22, Xq24 and Xp22 (see Table 3).…”
Section: The Examination Of Pedigrees Segregation Analysis and Linkamentioning
confidence: 67%
“…A number of 'second generation' linkage analyses on growth, which mainly involved larger sample sizes (up to 434 pedigrees and 4130 individuals (30)) are narrowing down on a smaller number of genetic regions that are associated with body height. Regions identified here attain high significance levels and can be replicated in various populations (28,30).…”
Section: The Examination Of Pedigrees Segregation Analysis and Linkamentioning
confidence: 99%
See 1 more Smart Citation